First-Trimester Cell-Free DNA Fetal Fraction and Birth Weight in Twin Pregnancies - Siegel, Molly R.; James, Kaitlyn; Bromley, Bryann; Koelper, Nathanael C.; Chasen, Stephen T.; Griffin, Laurie; Roman, Ashley S.; Limaye, Meghana; Ranzini, Angela; Clifford, Caitlin; Biggio, Joseph R.; Subramaniam, Akila; Seasely, Angela R.; Page, Jessica M.; Nicholas, Sara S.; Idler, Jay; Rao, Rashmi; Shree, Raj; McLennan, Graham; Dugoff, Lorraine; on behalf of the Twin cfDNA Study Consortium (American Journal of Perinatology, 2024)
The relationship between fetal fraction and birth weight in twin gestations is poorly understood. This study aimed to investigate the relationship between first-trimester cell-free DNA (cfDNA) fetal fraction and birth weight <10th percentile in twin gestations.This is a planned secondary analysis of the Twin cfDNA Study, a 17-center retrospective cohort of twin pregnancies screened for aneuploidy using cfDNA in the first trimester from December 2011 to February 2022, excluding those with positive screen results for chromosomal aneuploidy. cfDNA testing was performed by a single laboratory using massively parallel sequencing. Baseline characteristics and birth weight of pregnancies with normal fetal fraction were compared with those with low (<5%) and high (>95%) fetal fraction using univariable analyses and multivariable regression.A total of 1,041 twin pregnancies were included. Chronic hypertension, elevated body mass index, and self-identified Black race were associated with fetal fraction <5th percentile. There was no difference in median fetal fraction between those with birth weight <10th percentile in at least one twin (median [interquartile range (IQR)] fetal fraction: 12.2% [9.8, 14.8] vs. those with normal birth weight (≥10th percentile) in both twins (median [IQR] fetal fraction: 12.3% [9.7, 15.2] for normal birth weight, p = 0.49). There was no association between high or low fetal fraction and birth weight <10th percentile for one (p = 0.45) or both (p = 0.81) twins, and there was no association between high or low fetal fraction and birth weight <5th percentile for one (p = 0.44) or both (p = 0.74) twins. The results were unchanged after adjustment for potential confounders.In this large cohort, there was no association between the extremes of cfDNA fetal fraction and birth weight <10th percentile, suggesting that first-trimester fetal fraction may not predict impaired fetal growth in twin gestations.
Keywords: cell-free DNA; twin gestations; birth weight